Cuffed pediatric endotracheal tubes—Outer cuff diameters compared to age‐related airway dimensions. Issue 4 (2nd January 2020) - Fischer, Martina; Grass, Beate; Kemper, Michael; Weiss, Markus; Dave, Mital H.
Abstract: Background: Reliable sealing of the pediatric airway requires appropriately sized tracheal tube cuffs. The aim of this study was to compare residual cuff diameters of pediatric tracheal tubes with pediatric airway dimensions. Methods: Cuff diameters of five different brands of locally marketed pediatric cuffed tracheal tubes with internal diameters of 3.0‐7.0 mm were measured at a cuff pressure of 20 cm H2 O and compared with cuff diameters indicated by their manufacturers. The latter values were compared to tracheal dimensions using the Motoyama and Khine formulas for cuffed tracheal tube size selection. Results: There is considerable heterogeneity in cuff diameters among pediatric tracheal tube brands, except for two brands from different manufacturers (Halyard and Parker Medical) which were identically designed. Cuffs made from polyurethane revealed fewer differences (91%‐118%) between measured and manufacturer‐indicated values for outer cuff diameters than did those made from polyvinylchloride (91%‐146%). Particularly in smaller sized tracheal tubes, cuffs did not reach 100% of the tracheal lateral diameter, while others were oversized in larger tracheal tubes, independent of the two formulas used for cuffed tracheal tube size selection. Cuff diameters indicated by the manufacturer corresponded to 86%‐188% of the median and 68%‐157% of the maximum mid‐tracheal lateral diameter of the corresponding upper age range. Conclusion: Our findings show that many of the cuff diameters of currently marketed tracheal tube brands lack an age‐related anatomical rationale. A proposal for age‐related anatomically based cuff diameters is provided for both recommendations for cuffed tracheal tube size selection in children.